Determinants of small & medium sized enterprises (SMEs) adoption of e-commerce - Ismail, Shahifol Arbi; Ismail, Noor Azizi; Hassan, Haslinda; Tahir, Agoos Munalis (Universiti Utara Malaysia, 2007)
As the catalyst of Malaysian economy, SMEs are expected to be at the forerunner in Information Technology (IT) adoption.Engaging in e-commerce seems to be the logical next step as e-commerce is cited to offer a lot of benefits to SMEs.The main objective of this study is to investigate the status of e-commerce adoption among SMEs in Malaysia. More specifically, this study aims to investigate the status of e-commerce adoption among SMEs and the factors contribute to the acceptance and use behavior of e-commerce among the managers of SMEs.Questionnaires which were based on UTAUT model were distributed to 1,216 SMEs from which 71 completed questioners were received.The findings indicated a low level of e-commerce adoption by SMEs with only 18 (31%) of the firms’ websites supported some sort of online transactions. Secondly, the results of regression analysis revealed that only Effort Expectancy is significantly and positively related to Behavioural Intention of using e-commerce by SMEs and this only partially supported original UTAUT model.Overall, this study has provided evidence that SMEs in Malaysia is still lagging behind in e-commerce adoption.